Second Undergraduate Health Science Research Seminar - New Straits Times (2008)
The Faculty of Medicine and Health Sciences of Universiti Putra Malaysia is organising its second Undergraduate Health Science Research Seminar today and tomorrow from 8.30am to 5om.